Banking Acquisition Model for Bank BJB(Case Study Acquisition of PD. BPR LPK in West Java) - Raisha, Raisha; Anggono, Achmad Herlanto (The Indonesian Journal of Business Administration, 2012)
To facilitate the credit loans for micro, small, and medium enterprise, the Government of West Java encourage the unification of business between PT. Bank Pembangunan Daerah Jawa Barat dan Banten (BJB) with PD. Bank Perkreditan Rakyat Lembaga Perkreditan Kecamatan (PD. BPR LPK). The Regulation of West Java Province No. 30 0f 2010 stated that BJB should increase their share ownership in PD. BPR LPK to 51%. BJB must do the acquisition of all PD. BPR LPK in West Java. The acquisition is in line with BJB’s plan to expand their bank’s network and credits. The analysis was carried upon twenty-one PD. BPR LPK in Cianjur, Garut, and Subang Regency. Before the acquisition, due diligence is conducted to assess the level of bank soundness. BJB will only acquire PD. BPR LPK that at least have moderately healthy predicate. To determine the acquisition cost, the valuations of company’s asset were done using book value valuation method. There are two scenarios that can be used as an acquisition model. In scenario A, BJB directly acquire all of the twenty-one PD. BPR LPK. In scenario B, each PD. BPR LPK in the same regency first conducting a merger, afterwards BJB will perform the acquisition of all merged PD. BPR LPK. The acquisition cost in scenario B is greater than the acquisition cost in scenario A, but scenario B has more bank networks. Scenario B is chosen with the total cost of acquisition Rp18,184,774,278. Keywords: PD. BPR LPK, acquisition, merger, bank soundness, book value valuation method